Formation of Self-Identity of Generation Z Through Instagram Social Media Amongst Students - Putri, Faradita Sari Eka; Khumayah, Siti; Nurfalah, Farida (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2023)
Technological progress is accelerating causing changes in various things. One of the impacts of technological advances is the rapid use of the internet. Talking about the internet, of course, it is very closely related to social media, Instagram for example. Instagram is one of the social media platforms that is currently loved by the public. Many active users on Instagram use this flatform as a medium of personal or business information. This study aims to find out how much influence Instagram has on the formation of self-identity that occurs in Generation Z in Communication Science Students FISIP Gunung Jati University, after knowing and using Instagram as a place to build self- identity. This was triggered by Generation Z who flocked to use Instagram as a place to build their identity. The Instagram application is also one of the applications that are popular with Generation Z because it has many interesting features in it. Generation Z often accesses Instagram features, causing them to experience changes in terms of attitudes, behavior, and even language. The method used is qualitative research, in this study using the type of qualitative research initiated by Sugiyono (2014) in (Kristanto, 2018) that the qualitative research method is a method based on the philosophy of post positivism used to examine the condition of an object that is natural rather than experimental. Data collection techniques are combined, data analysis is inductive/qualitative and qualitative research findings emphasize meaning rather than generalization. The conclusion of the results obtained from this study is that generation Z in using Instagram is meant to be in intense use. The motive shown by generation Z is the formation of self-identity by performing selves. They have certain goals that will ultimately affect the formation of their Self-Identity.